Aid to life – Montessori pedagogy in the service of autism spectrum children - Monika Pawluczuk-Solarz (Problemy Wczesnej Edukacji)
This article explores the feasibility of implementing Montessori principles outside traditional Montessori environments, focusing on children with autism whose families cannot afford Montessori schooling. It examines whether Montessori education can effectively address the needs of autistic children in non-Montessori settings. The author, a Montessori educator, describes her efforts to adapt Montessori methods in diverse environments, including public kindergartens, schools, therapeutic centres, and extracurricular activities. The research refers to the growing prevalence of autism, as noted by the World Health Organization, and the necessity of inclusive educational approaches. The author presents practical examples of children’s interactions with Montessori materials and innovative adaptations of Montessori philosophy to suit various settings. Special attention is given to activities inspired by Montessori’s Great Stories, demonstrating their potential in engaging children from different backgrounds. The paper argues that Montessori education should extend beyond specialized institutions to benefit a broader range of children, particularly those on the autism spectrum. It highlights the importance of preserving the core tenets of Montessori pedagogy – individual, spontaneous activity, and holistic human development – while adapting to external conditions. The article provides valuable insights into integrating Montessori principles in non-traditional settings, advocating for more inclusive educational practices.